EVALUASI SISTEM PENGAMAN PANTAI DI BALI SELATAN UNTUK MENGATASI TANTANGAN PERUBAHAN IKLIM - Candrayana, Kadek Windy; Sinarta, I Nengah; Putu Eryani, I Gusti Agung (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2023)
This climate change impacts the coast of Indonesia, which causes erosion and tidal flooding. This coastal damage significantly affects vital areas in the form of tourist areas, such as on the south coast of Bali. The erosion rate on Bali's beaches currently reaches 2 m/year and dramatically impacts the existence of beach tourism objects in Bali. Seawalls and revetments dominate coastal protection structures built from the 1990s. The existing system is experiencing problems, namely tidal flooding and runoff at the building's crest. The method analyzes sea-level changes over time (time series) and numerical simulations with CMS-Wave to obtain wave heights in the structure. Extreme water level (Extreme Coastal Water Level) is calculated from the creep due to wave height, sea level rise, tides, and storms. The results of this study indicate that the rising water level in 2022 will cause 53.80% of buildings to experience overtopping. In the next 20 years (2042), the percentage of buildings experiencing overtopping will increase to 67.08%.